What childhood characteristics predict psychological resilience to economic shocks in adulthood? - Powdthavee, Nattavudh (J Econ Psychol, 2014)
This paper investigates whether people’s psychological resilience to one of the most important economic shocks – job loss – can be predicted using early childhood characteristics. Using a longitudinal data that tracked almost 3000 children into adulthood, we showed that the negative effect of unemployment on mental well-being and life satisfaction is significantly larger for workers who, as adolescents, had a relatively poor father-child relationship. Maternal unemployment, on the other hand, is a good predictor of how individuals react psychologically to future unemployment. Although the results should be viewed as illustrative and more research is needed, the current article provides new longitudinal evidence that psychological resilience to job loss may be determined early on in the life cycle.